The Impact of School from Home in Teaching and Learning English for Young Learners - Effinaftalia Thisa Gracia Tarigan (Journal of Educational Study, 2021)
The objectives of this study were to examine the impact of school from home in teaching and learning English for young learners. This study employed a case study approach, which is an embedded single-case design. A set of questionnaires was distributed to twelve young learners in the fourth grade of an elementary school in Singaraja and one English teacher. The young learners in this study were selected with purposive sampling, where participants were selected based on their parents' and teachers’ consent. Furthermore, an interview was also conducted with one English teacher from an elementary school in Singaraja to obtain the supplementary data. The findings indicate that the impact of school from home in teaching and learning English had some positive and negative impacts. Therefore, this study ends with suggestions for teachers and parents during school from home.